2019
DOI: 10.1097/md.0000000000014610
|View full text |Cite
|
Sign up to set email alerts
|

Acupoint catgut embedding for the treatment of obesity in adults

Abstract: Background: Obesity is the biggest chronic health problems among adults worldwide and the main predisposing factor in many types of systemic diseases such as hypertension, diabetes, and so on. In clinical reports on Traditional Chinese Medicine, acupoint catgut embedding has been shown to improve various clinical indicators for diseases including obesity and body mass index (BMI), but the safety of this and method has not been assessed. Methods: This systematic review s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The ability to conserve time and costs makes AcE an attractive treatment method. Although side effects such as local inflammation, pain, callosity, and discomfort may occur for several days following treatment, this method has been widely used for the management of obesity (22). Zusanli (ST36) is most commonly used for the treatment of pain, lower limb issues and gastrointestinal disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to conserve time and costs makes AcE an attractive treatment method. Although side effects such as local inflammation, pain, callosity, and discomfort may occur for several days following treatment, this method has been widely used for the management of obesity (22). Zusanli (ST36) is most commonly used for the treatment of pain, lower limb issues and gastrointestinal disorders.…”
Section: Introductionmentioning
confidence: 99%
“…To reach a satisfying outcome, this procedure needs to be repeated every 3 to 4 weeks at least for 2 months. [8] Although AEM has been originated and developed in China, by attending other countries such as South Korea, Mexico, and Indonesia it was expected to develop different methods and indications; however, our literature review showed no significant difference between method of performing AEM in different countries. [9–12] Generally, 3 types of embedding threads are available: natural threads including collagen or chitosan threads, synthetic polymer threads including polylactic acid-glycolic acid or polydioxanone threads, and bioactive threads including antimicrobial, silver nanoparticle, or sustained-release threads.…”
Section: Methods and Thread Typesmentioning
confidence: 88%
“…Researches have indicated that ACE can effectively treat simple obesity by regulating the neuroendocrine system, intestinal flora, and leptin level. [ 43 , 44 ] Acupuncture combined with ACE offers advantages over standard acupuncture, including prolonged effects, enhanced patient compliance, and more robust long-term effects. [ 45 ] Previous studies have demonstrated the synergistic effect of acupuncture combined with ACE in the treatment of simple obesity, resulting in superior curative effect compared with acupuncture alone or ACE alone.…”
Section: Discussionmentioning
confidence: 99%